ASSESSMENT OF CUSTOMER RELATIONSHIP MANAGEMENT LEVEL BASED ON CUSTOMER SATISFACTION INDEX PERCEPTION OF TEA DRINKS - Tri Apriliyanto, Yohandika; Arya Ash Shidik, Beta; Ningsih, Sri (Industri Inovatif : Jurnal Teknik Industri, 2026)
Tea may be served hot or cold, which makes it quite popular among the Indonesians. Teh Kota is one of the most well-known tea franchise companies. The competition from other franchisees has produced swings in client numbers at Teh Kota franchise. Research has been conducted on the impact of item quality on client fulfillment utilizing the CSI approach and identifying the components that influence customer satisfaction in the context of CRM. In a sample of 100 respondents, individuals encountered by the researcher were included based on suitability, using a non-probability sampling strategy with a random sampling approach. With a correlation value of 0.696, which shows a strong association between the independent and dependent variables, the study discovered a considerable impact of product quality on customer satisfaction. Service quality influences 48.5% of customer happiness, according to the R2 value of 0.485. The overall customer satisfaction level at the Tulis and Kandeman branches of Teh Kota is considered very satisfactory, with a percentage value of 86.32%. The findings suggest that product quality is crucial in enhancing customer satisfaction at Teh Kota franchises in Batang Regency